2023
DOI: 10.1186/s43591-023-00054-6
|View full text |Cite
|
Sign up to set email alerts
|

Bringing sex toys out of the dark: exploring unmitigated risks

Abstract: A majority of American adults report having used sex toys, which, by design, interact with intimate and permeable body parts yet have not been subject to sufficient risk assessment or management. Physical and chemical data are presented examining potential risks associated with four types of currently available sex toys: anal toy, beads, dual vibrator, and external vibrator. A standardized abrasion machine made real-time breakdown of products into microplastics and nanoplastics. The microplastics from the sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a recent study, scientists tested 4 types of sex toys: dual vibrators, external vibrators, anal toys and beads all of which interact with intimate and permeable parts of the body and reported that anal toys release the most plastic bits, followed by beads, dual vibrators, and external vibrators, the release of microplastics and nanoplastics by sex toys during use can have negative consequences for reproductive health [ 30 ]. However we found just one case report directly linking plastic use and MNPs to fertility and negative pregnancy outcomes in humans.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, scientists tested 4 types of sex toys: dual vibrators, external vibrators, anal toys and beads all of which interact with intimate and permeable parts of the body and reported that anal toys release the most plastic bits, followed by beads, dual vibrators, and external vibrators, the release of microplastics and nanoplastics by sex toys during use can have negative consequences for reproductive health [ 30 ]. However we found just one case report directly linking plastic use and MNPs to fertility and negative pregnancy outcomes in humans.…”
Section: Methodsmentioning
confidence: 99%